Increasing Interest and Learning Outcomes of Fifth-Grade Students in Science Subjects Using Quizizz Media with a Scientific Approach at SDN 03 Bengkayang - Owen, Mickael Febrianto; Silvester (Institut of Shanti Bhuana, 2024)
This research aims to increase students' interest and learning outcomes in science subjects. Using Quizizz media with a scientific approach. The method applied in this research is Classroom Action Research. With 30 students consisting of 15 male students and 15 female students. This research was carried out as an effort to overcome various problems experienced in the classroom. This method is implemented in four stages, namely planning implementation, and observing and reflecting on actions. These four stages are cycles that occur repeatedly and are carried out in the same stages and are focused on using the Quizizz media with a scientific approach. Based on the results of research that has been carried out on the science learning process, it can be concluded that there is an increase in student interest and learning outcomes in science subjects using Quizizz media with a scientific approach. In the first cycle, the N-Gain calculation was carried out on students' interest in learning, obtaining an average score of 85.6 with a score of 57.2, which was in the quite effective category, then the students' learning results were 27 out of 30 students obtained a completeness score of ≥70 and the results N-Gain calculations obtained an average value of 82 with a score of 56.2 in the quite effective category. In cycle II, the N-Gain calculation of interest in learning averaged 93 and reached a score of 80.9% in the effective category. The results of the N-Gain calculation resulted in an average learning score of 91.36 and a score of 81.39%.